A Framework for Upgrading Contaminated Urban Land and Soil by Nature-Based Solutions: Demonstration with a Swedish Case - Shaswati Chowdhury; Yevheniya Volchko; Jenny Norrman (Urban Science)
To move towards a circular economy and to meet the upcoming EU soil health legislation, both contaminated land and contaminated soil should be acknowledged as fragile and valuable resources to be restored and recycled to provide essential ecosystem services to humans. Underused, often contaminated land can be returned to beneficial use as urban greenspace (UGS) with the help of gentle remediation options (GROs). GROs are plant-, fungi-, bacteria-, and soil amendments-based risk management mechanisms that can also simultaneously improve soil functions and the provision of ecosystem services. This study (i) presents a framework including tools and methods for exploring opportunities for transforming brownfields to UGS using GROs to deal with soil contamination, (ii) demonstrates its application for a case study site in Gothenburg, Sweden, and (iii) presents stakeholders’ views on the suggested framework. This framework can support the transition of brownfields to UGS while recycling both land and soil and increasing the market value of the site and its surroundings. Stakeholders found the suggested framework useful but identified some challenges for its practical implementation, mainly associated with financial aspects and the existing practice and level of knowledge. Stakeholders also identified the need for additional practical tools to (a) make predictions about the time required for GROs to reach acceptable risk levels, (b) monetize non-market benefits such as ecosystem services for communicating benefits to decision-makers, and (c) provide support for plant and soil amendment selection for various GROs and contaminants.